2014
DOI: 10.1039/c4dt01836b
|View full text |Cite
|
Sign up to set email alerts
|

Thermochromism, stability and thermodynamics of cobalt(ii) complexes in newly synthesized nitrate based ionic liquid and its photostability

Abstract: In this work a 1-(2-hydroxyethyl)-3-methylimidazolium nitrate ionic liquid, [HO(CH2)2mim]NO3, has been synthesized in order to serve as a new thermochromic material upon addition of cobalt(II) ions. Spectrophotometric measurements of a series of cobalt(II) nitrate and cobalt(II) chloride solutions in [HO(CH2)2mim]NO3 at 298.15, 308.15, 318.15, 328.15, and 338.15 K, were performed. Based on the recorded spectra, the overall stability constants and thermodynamic parameters for the cobalt(II) associations with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…On the other hand, the [Sal] À showed UV absorption at a broader range between 200 and 335 nm, with three absorption maxima at 205, 236, and the lowest at 303 nm. Since the UV radiation of used lamp below of closely 275 nm cannot pass through Pyrex glass, 25 no direct photolysis of [bmim] + could be expected. Also, observing the radiation of lamp which passed through the wall of the reactor and the absorption spectrum of absorbed radiation by [Sal] À in the range of 275 to 335 nm, a direct photolysis of the [Sal] À could be possible.…”
Section: Uva Photodegradation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the [Sal] À showed UV absorption at a broader range between 200 and 335 nm, with three absorption maxima at 205, 236, and the lowest at 303 nm. Since the UV radiation of used lamp below of closely 275 nm cannot pass through Pyrex glass, 25 no direct photolysis of [bmim] + could be expected. Also, observing the radiation of lamp which passed through the wall of the reactor and the absorption spectrum of absorbed radiation by [Sal] À in the range of 275 to 335 nm, a direct photolysis of the [Sal] À could be possible.…”
Section: Uva Photodegradation Studiesmentioning
confidence: 99%
“…Thus, it is very important to nd an efficient method for a complete and safe removal of ionic liquids from the environment. [23][24][25] The advanced oxidation processes (AOPs), for example, UVA/H 2 O 2 , UVA/Fe 2+ /H 2 O 2 , and UVA/TiO 2 are potentially useful for wastewater treating because they generate hydroxyl radicals, [26][27][28] a powerful nonspecic oxidant, and can provide an almost total degradation. 29 Among numerous AOPs, Fenton's process is one of the promising technologies because of the high oxidation potential and relatively low cost.…”
Section: Introductionmentioning
confidence: 99%
“…1,[9][10][11][12] While ionic liquid systems with thermochromism related to changes in coordination of the metal centre have previously been reported, this has either been in the presence of additives or molecular solvents, or the magnetic properties were not investigated. [13][14][15][16][17] Here, we report on solutions of cobalt(II)isothiocyanate in thiocyanate ILs that show reversible switching of the cobalt(II) speciation from tetrahedral [Co(NCS)4] 2at room temperature to octahedral [Co(NCS)6] 4at temperatures around 233 K. These temperature-dependent changes in the co-ordination environment are accompanied by reversible changes in colour (blue to red) and by significant changes of the effective magnetic moment of these fluids. The IL acts as a reservoir for the thiocyanate anions, enabling a reversible equilibrium, which in turn results in a reversible temperature-dependent switching of the coordination environment; hence a reversible switching of the magnetic moment.…”
Section: Temperature-dependent Switching Of Paramagnetism Of a Cobaltmentioning
confidence: 99%
“…Ionic liquids (ILs) are a subject of active research in the field of alternative solvents, being promoted as “green chemistry” replacements to traditional solvents used in industry . The great interest in these compounds relies on their attractive properties such as low vapour pressures and flammability, chemical and thermal stability, high ionic conductivity, wide electrochemical potential window and ability to behave as catalysts …”
Section: Introductionmentioning
confidence: 99%
“…1 The great interest in these compounds relies on their attractive properties such as low vapour pressures and flammability, chemical and thermal stability, high ionic conductivity, wide electrochemical potential window and ability to behave as catalysts. [2][3][4] Only few studies have reported on the environmental fate of ILs. 5 Photochemistry is a potentially important attenuation route influencing the fate of ILs in surface waters.…”
Section: Introductionmentioning
confidence: 99%